Endogenous Institutional Change and Economic Development: A Micro-Level Analysis of Transmission Channels - Michael Grimm; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
There is a well-known debate about the role of institutions in explaining the long-term development of countries. We believe there is value-added to consider the institutions hypothesis at the micro level within a country to analyze the exact transmission channels linking endogenous institutional change to development outcomes. Given the central importance of agricultural productivity improvements for initiating the process of economic development, we focus on the transmission mechanisms that lead to the emergence of institutions relevant for agricultural development, thereby incorporating insights from the literatures on demographic influences of institutional change, induced innovations, as well as the central role of land rights in our analysis. Our main argument is that in conditions of relative land abundance, geographic factors influence rural-rural migration flows to geographically well-endowed regions which in turn give rise to migration-induced land scarcity. Land scarcity in turn, provides incentives to formalize landownership. Eventually, formalized land rights increase investment in land and enhance the adoption of new and better technologies promoting agricultural growth and economic development. We provide empirical evidence for this hypothesis using longitudinal village and household survey data from Indonesia.
Keywords: K11; O12; Q12; 330; Geography; migration; land titles; institutions; agricultural development; Indonesia